[2 + 2 + 2] cyclotrimerisation as a convenient route to 6N-doped nanographenes: a synthetic introduction to hexaazasuperbenzenes12. Issue 39 (3rd May 2017) - Wijesinghe, Lankani P.; Perera, Sarath D.; Larkin, Eugene; Ó Máille, Gearóid M.; Conway-Kenny, Robert; Lankage, Buddhie S.; Wang, Longsheng; Draper, Sylvia M.
Abstract : Novel, fully and 5/6 th partially-fused, hexaazasuperbenzenes are obtained using a variety of oxidative cyclodehydrogenation conditions. Their spectroscopic properties are compared. Abstract : 6N-containing polyphenylene precursors were generated via [2 + 2 + 2] cyclotrimerisation. On methoxy substitution complete ring-closure can be achieved ( via FeCl3 -mediated oxidative cyclodehydrogenation) to give asymmetric and C 3v symmetric hexaazasuperbenzenes. Investigations using DDQ/H + mediated conditions reveal this to be a promising alternative and selective route to partial cyclodehydrogenation.